PRINSIP-PRINSIP NEGARA HUKUM DALAM AL-QURAN DAN AS-SUNAH DAN IMPLEMENTASINYA DI INDONESIA - Hamimah, Siti (JURNAL AKTA YUDISIA, 2017)
Abstract As known in the Republic of Indonesia, which is the basis of its legal life is Pancasila, both as outlined in the preamble nor the body of the Constitution of 1945. And therefore the whole law dibujo by the state or government in the broadest sense, is not permitted contrary to God's law, even more so, any order made law, must berksaran above and diktunjukan for the implementation of the law of God. It en el mar as a logical consequence than the precepts on God in Pancasila, which is legally binding, to the people and the government to put it into practice. Inside the Pancasila enviar, religion has a central position. In it, embodied the principle that puts religion and to the Lordship of the Almighty in a position first and foremost. Therefore, it can not not, religion, also, must, admittedly, has a position, which is important, main, deep, effort, reform, law, criminal, national. Therefore, the authors are interested, write to, approach, law, Islam, about, practice, constitutional, that is, Indonesia, by referring, on the principles, contained in the Qur'an and the Sunnah of the ProphetKeywords : Prinsiple, Pancasila, civil law